2016
DOI: 10.1063/1.4963708
|View full text |Cite
|
Sign up to set email alerts
|

Are dangling bond centers important interface traps in 4H-SiC metal oxide semiconductor field effect transistors?

Abstract: Silicon carbide (SiC) based metal-oxide-semiconductor field-effect transistors (MOSFETs) have great promise in high power and high temperature applications. Unfortunately, effective channel mobilities remain disappointingly low, typically about 30 cm2/Vs. A major contributor to the disappointing effective channel mobilities is the presence of substantial densities of interface traps at the SiC/SiO2 interface. Many investigators have invoked silicon or carbon dangling bonds to be the dominating source of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…3b interface. [16][17][18][20][21][22]34 However, those studies reported on an isotropic g-factor in the range of g ≈ 2.0023 − 2.0031. 17,20 It is not clear at this point why there is such a discrepancy between the observed g-factors.…”
Section: B Comparison Of the Different Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…3b interface. [16][17][18][20][21][22]34 However, those studies reported on an isotropic g-factor in the range of g ≈ 2.0023 − 2.0031. 17,20 It is not clear at this point why there is such a discrepancy between the observed g-factors.…”
Section: B Comparison Of the Different Samplesmentioning
confidence: 99%
“…[16][17][18][20][21][22] A recent study by M.A. Anders et al ruled out the presence of dangling bond defects at the SiC/SiO 2 interface 34. However, their argumentation was based on the absence of resonance lines additional to the dominant defect spectrum which was assigned to the V Si based on its isotropic g-factor.…”
mentioning
confidence: 99%
“…8,16,37,38 Several EDMR studies performed at interfaces produced by thermal oxidation linked the observed defect to the V Si center, based on the isotropic nature of the g-factor. 11,39,40 The study of Cochrane et al 11 resolved the HF structure of the V Si using the adiabatic fast passage EDMR technique. The fast passage technique for EPR measurements was pioneered by Hyde and Weger in the 1960s and 1970s and relates to a scan rate of sufficient speed that the electron spins are not able to relax between modulation sweep cycles.…”
Section: Introductionmentioning
confidence: 99%
“…11,41,42 However, while this study identified the V Si as the defect observed by fast passage EDMR, the other referenced studies used a conventional detection scheme (without fast passage) and showed a dramatically different spectrum. 39,40 This is suggestive of a time component to the measurement resulting in different defects probed as a result of a) j.cottom.12@ucl.ac.uk 0021-8979/2018/124(4)/045302/10/$30.00…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation